2022
DOI: 10.1002/jcsm.13143
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the prevalence and correlation of mild cognitive impairment in sarcopenia

Abstract: Sarcopenia is a progressive skeletal muscle disorder involving the loss of muscle mass and function, associated with an increased risk of disability and frailty. Though its prevalence in dementia has been studied, its occurrence in mild cognitive impairment (MCI) has not been well established. As MCI is often a prelude to dementia, our study aims to investigate the prevalence of MCI among individuals with sarcopenia and to also ascertain whether sarcopenia is independently associated with MCI. The Cochrane Lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 56 publications
3
25
0
1
Order By: Relevance
“…Consequently, older adults with MCI are at risk of developing sarcopenia due to decreased physical activity and malnutrition. These findings align with previous research indicating an association between MCI and sarcopenia [ 87 , 91 ]. The prevalence of sarcopenia was found to be 5.5 times higher in older adults with MCI compared to those with normal cognitive function [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, older adults with MCI are at risk of developing sarcopenia due to decreased physical activity and malnutrition. These findings align with previous research indicating an association between MCI and sarcopenia [ 87 , 91 ]. The prevalence of sarcopenia was found to be 5.5 times higher in older adults with MCI compared to those with normal cognitive function [ 87 ].…”
Section: Discussionsupporting
confidence: 93%
“…Older adults with MCI often experience reduced physical activity levels [ 88 , 89 ], which is linked to decreased grip strength and slower walking speed [ 90 ]. Additionally, individuals with impaired brain function may suffer from anorexia, resulting in reduced food intake and malnutrition [ 91 ]. Consequently, older adults with MCI are at risk of developing sarcopenia due to decreased physical activity and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary function decline may decrease cognitive performance via hypoxia, decreased neurotransmitter function, increased systemic inflammatory processes, or a combination of various factors [9,10]. Although numerous research have examined that sarcopenia may be a potential contributing factor to cognitive impairment [34,35], our findings indicate a positive correlation between diminished cognitive abilities and increased susceptibility to sarcopenia. Likewise, a longitudinal study also found that any cognitive impairment predicted decreased handgrip strength [36].…”
Section: Discussionmentioning
confidence: 64%
“…Aging is a challenging issue that modern society have to confront, and plays an important role in both sarcopenia and cognitive impairment. Previous evidences demonstrated the association between these two conditions, populations with sarcopenia have a higher risk of cognitive impairment 29 . In addition, this correlation is independent of factors such as gender, region, and race [30][31][32] .…”
Section: Discussionmentioning
confidence: 96%